2020
DOI: 10.3389/fped.2020.00226
|View full text |Cite
|
Sign up to set email alerts
|

Low Body Weight Predicted Bradycardia and Desaturation in Retinopathy of Prematurity Surgeries: A Retrospective Cohort Study

Abstract: Background: As a leading cause of childhood blindness, the epidemic of retinopathy of prematurity (ROP) in China is characterized by advanced stage of ROP in more mature infants than those in the West. More advanced stage of disease necessitates more complicated surgical procedures and consequently exposure to general anesthesia. These ex-prematurely born infants are at risk of developing desaturation especially after surgery under general anesthesia. Physical status, anesthetic management and surgical profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Although not statistically significant, we found that most of the infants who developed intraoperative and postoperative complications had ASA III and above risk scores. Similar to ASA, LBW has been reported as a risk factor for the development of complications (13). We found that LBW was a risk factor for the development of both intraoperative and postoperative complications.…”
Section: Discussionsupporting
confidence: 70%
“…Although not statistically significant, we found that most of the infants who developed intraoperative and postoperative complications had ASA III and above risk scores. Similar to ASA, LBW has been reported as a risk factor for the development of complications (13). We found that LBW was a risk factor for the development of both intraoperative and postoperative complications.…”
Section: Discussionsupporting
confidence: 70%
“…4 The incidence of bradycardia is decreased among pediatric patients premedicated with atropine and dexmedetomidine, airway protection with an endotracheal tube, and high body weight. 14,15 There was a limited study conducted on bradycardia after induction of anesthesia among pediatric patients. This may increase the failure rate in the proper diagnosis and management, as well as limit adherence to perioperative standards to handle pediatric surgical patients.…”
Section: Introductionmentioning
confidence: 99%